Chronic Constipation in the United States: Results From a Population-Based Survey Assessing Healthcare Seeking and Use of Pharmacotherapy. (23rd June 2020) - Oh, Sun Jung; Fuller, Garth; Patel, Devin; Khalil, Carine; Spalding, William; Nag, Arpita; Spiegel, Brennan M. R.; Almario, Christopher V.
Abstract : OBJECTIVES: Chronic idiopathic constipation (CIC) is characterized by unsatisfactory defecation and difficult or infrequent stools. CIC affects 9%–20% of adults in the United States, and although prevalent, gaps in knowledge remain regarding CIC healthcare seeking and medication use in the community. We recruited a population-based sample to determine the prevalence and predictors of (i) individuals having discussed their constipation symptoms with a healthcare provider and (ii) the use of constipation therapies. METHODS: We recruited a representative sample of Americans aged 18 years or older who had experienced constipation. Those who met the Rome IV criteria for irritable bowel syndrome and opioid-induced constipation were excluded. The survey included questions on constipation severity, healthcare seeking, and the use of constipation medications. We used multivariable regression methods to adjust for confounders. RESULTS: Overall, 4, 702 participants had experienced constipation (24.0% met the Rome IV CIC criteria). Among all respondents with previous constipation, 37.6% discussed their symptoms with a clinician (primary care provider 87.6%, gastroenterologist 26.0%, and urgent care/emergency room physician 7.7%). Age, sex, race/ethnicity, marital status, employment status, having a source of usual care, insurance status, comorbidities, locus of control, and constipation severity were associated with seeking care ( P < 0.05). Overall, 47.8% of respondents were taking medication to manage their constipation: over-the-counter medication(s) only, 93.5%; prescription medication(s) only, 1.3%; and both over-the-counter medication(s) and prescription medication(s), 5.2%. DISCUSSION: We found that 3 of 5 Americans with constipation have never discussed their symptoms with a healthcare provider. Furthermore, the use of prescription medications for managing constipation symptoms is low because individuals mainly rely on over-the-counter therapies.